Factors Influencing the Knowledge Seekers in Adopting the Knowledge Management System (KMS) - Assegaff, Setiawan (UI Scholars Hub, 2015)
One indication of KMS success is when the knowledge seeker actively access the knowledge stored within the system’s repository. Unfortunately, studies that specifically designed to provide more understanding about the behavior of the knowledge seeker with regard to their acceptance of KMS are still quite rare. The purpose of this study is to investigate the factors that influence the behavior of knowledge seeker(s) in KMS acceptance. A research model for this study was developed using the Theory of Reasoned Action (TRA), and the data was collected from 125 knowledge seekers from three companies in Indonesia. By utilizing the Squares Structural Equation Modeling (SEM) techniques with Smart PLS V2 software, the results of the statistical analysis confirmed that there is a positive correlation between the factors of management, effort and social relationship and the intention of knowledge seeker(s) in KMS acceptance. However, the correlation between the benefit factor and the intention of knowledge seeker(s) in KMS acceptance was not found.